2009
DOI: 10.1158/1940-6207.capr-09-0094
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Plasma of Pancreatic Ductal Adenocarcinoma Patients as Novel Blood-Based Biomarkers of Disease

Abstract: Development of minimally invasive biomarker assays for early detection and effective clinical management of pancreatic cancer is urgently needed to reduce high morbidity and mortality associated with this malignancy. We hypothesized that if aberrantly expressing microRNAs (miRNA) in pancreatic adenocarcinoma tissues are detected in blood plasma, then plasma profiling of these miRNAs might serve as a minimally invasive early detection biomarker assay for this malignancy. By using a modified protocol to isolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
376
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(402 citation statements)
references
References 39 publications
14
376
2
2
Order By: Relevance
“…Additionally, the characteristics of miRNAs, such as tissue-specific miRNA signatures and the availability of numerous copies/cells, indicated potential advantages as biomarkers compared to those of other nucleic acids, such as circulating DNA and mRNA. An increasing number of studies also suggest the potential use of miRNAs in the early detection of patients with several malignancies, such as gastric, pancreatic, colorectal and breast cancer (6)(7)(8)(9). Recent studies have focused ons the role of circulating miRNAs in the plasma of CRC patients (7,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the characteristics of miRNAs, such as tissue-specific miRNA signatures and the availability of numerous copies/cells, indicated potential advantages as biomarkers compared to those of other nucleic acids, such as circulating DNA and mRNA. An increasing number of studies also suggest the potential use of miRNAs in the early detection of patients with several malignancies, such as gastric, pancreatic, colorectal and breast cancer (6)(7)(8)(9). Recent studies have focused ons the role of circulating miRNAs in the plasma of CRC patients (7,18).…”
Section: Discussionmentioning
confidence: 99%
“…Mitchell et al (4) clearly demonstrated that circulating miRNAs originate from cancer tissues (4). Additional studies have demonstrated the presence of circulating miRNAs and their potential use as novel biomarkers of various types of cancer, such as pancreatic (6), colorectal (7), breast (8) and gastric cancers (9). These studies have provided new opportunities for a non-invasive examination for the early diagnosis of various types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…8,[58][59][60][61][62][63][64] Expression profiling has identified several miRNAs aberrantly expressed in PC cell lines and clinical tissue samples that were correlated with clinical outcome. [65][66][67][68][69][70][71][72][73][74] Alterations in miRNA expression profiles might be useful in the prediction of the individual response to chemotherapy and may even be targets for therapies to increase chemosensitivity.…”
Section: Micrornas As Epigenetic Targetsmentioning
confidence: 99%
“…Every cancer investigated has a distinct miRNA signature and deregulated levels of miRNAs have been detected in body fl uids of patients, including those with lymphoma, [11] leukemia, [12] colon, [13] breast, [14] prostate, [15] ovarian, [16] pancreatic, [17] gastric, [18] and lung cancer. [19] In the context of brain tumors, recent studies have demonstrated a signifi cant presence of certain miRNAs in CSF samples from patients with central nervous system lymphoma, glioma, and metastatic brain cancers.…”
Section: Introductionmentioning
confidence: 99%